Research Progress in Advanced Treatment Technology of Municipal Reclaimed Water in China - LIANG Yaoyun; HUANG Xiao (Renmin Zhujiang)
Reclaimed water,as the second source of water in cities,is of great significance in alleviating the crisis of water resources and promoting the utilization of sewage resources.Currently,major cities are accelerating the renovation of sewage treatment plants or the construction of reclaimed water plants,fully tapping the utilization potential of sewage resources.Firstly,this review introduced the current situation of reclaimed water reuse,the operation mode of reclaimed water,and the requirements for reclaimed water quality.Focusing on the advanced treatment technology of reclaimed water,the review systematically sorted out the removal objects,water purification mechanisms,engineering cases,and development directions of various technologies,so as to analyze the experience and shortcomings of the application of advanced treatment technology of reclaimed water and propose development ideas.Besides,the selection of future reclaimed water processes should be reuse-oriented,taking into account factors such as local natural conditions,economic development,and infrastructure construction,while strengthening independent research and development to promote the application of reclaimed water treatment equipment with independent intellectual property rights.